Control, regulation and command system of hydronic radiant floors heating by wireless and energy harvesting sensors and actuators - Batista, G. (2019)
This paper presents the development of an innovative control, regulation and command system for hydronic radiant floors, more flexible and efficient that guarantees a better thermal comfort to the user and simultaneously improves the energy efficiency of this type of heating system. The majority of the actual control of hydronic radiant floors is done by thermostats that measure the air temperature and control the actuators (pumps and valves) in order to maintain the room at the specified temperature. These systems requires the frequent adjustment of thermostats set-point in order to obtain thermal comfort as it depends on other factors than just the air temperature, such as, the air humidity, external environmental conditions, radiant temperature, among others. This paper presents a control, regulation and command solution that requires minimum user intervention, as the user only has to choose the desirable thermal comfort level. The control algorithm is based on the calculation of PMV (Predicted Mean Vote) index as defined on Thermal Comfort Standard ISO 7730. Another advantage of the proposed system is related to the wireless and energy harvesting sensors and actuators that provide much more flexibility to the system.